FRI0572 Ultrasound Features of Hand Osteoarthritis (OA) Can be Reliably Scored by Use of Reference Atlases. (9th June 2015) - Mathiessen, A.; Robinson, P.S.; Haugen, I.K.; Hammer, H.B.
Abstract : Background: A previously proposed scoring system for assessment of ultrasound (US) features of hand osteoarthritis (OA) includes osteophytes (OP), grey scale synovitis (GS) and power Doppler (PD) signals. However, US is by some considered to be an operator-dependent technology with moderate reliability. Objectives: By use of US atlases as background [1, 2] to examine intra- and inter-reader reliability of US assessments (OP, GS and PD) of still images by sonographers with varying degree of US experience. Methods: Stored US images of hand OA joints (carpometacarpal 1, metacarpophalangeal 1-5, proximal interphalangeal 1-5 and distal interphalangeal 2-5) with different degrees of OP (n=133), GS (n=103) and PD (n=20) pathologies were selected and randomized by IKH. With digital US atlases available, three physicians (one inexperienced (PSR), one moderate experienced (AM) and one highly experienced (HBH)) separately scored the anonymised images twice with at least one week interval. All US features were scored on semi-quantitative 0-3 scales. Intra- and inter-reader reliability was assessed by use of kappa (κ; data not shown), weighted kappa (κ w ), percentage exact agreement (PEA) and percentage close agreement (PCA; scores within ±1 interval). Scores above 0.60 are considered good and scores above 0.80 are very good. Results: The table provides results from the reliability exercise. With use of US atlas, intra-reader reliability was excellent for OP (κ w 0.93–0.95, PEA 100%), GS (κ w 0.86–0.91, PEA 83, 5%–100%) and PD (κ w 0.95–1.00, PEA 100%). The inter-reader reliability was very good for OP (κ w 0.76–0.93, PEA 73, 7%–91.7%) and PD (κ w 0.80–0.95, PEA 80.0%–95.0%), and good for GS (0.61–0.74, PEA 68.9%–80.6%). The average (range) PCA for both intra- and inter-reader reliability was 99.0% (83.5%–100%). Conclusions: This encouraging reliability exercise demonstrates that with current available US atlases of OP, GS and PD, one can obtain good to excellent agreement on US scorings even with limited experience. Since US is an operator dependent modality, we suggest that an atlas should be included in US studies of hand OA patients. References: Hammer HB, Bolton-King P, Bakkeheim V, et al. Examination of intra and interrater reliability with a new ultrasonographic reference atlas for scoring of synovitis in patients with rheumatoid arthritis. Ann Rheum Dis. 2011 Nov; 70(11):1995-1998. Mathiessen A, Haugen IK, Slatkowsky-Christensen B, et al. Ultrasonographic assessment of osteophytes in 127 patients with hand osteoarthritis: exploring reliability and associations with MRI, radiographs and clinical joint findings. Ann Rheum Dis. 2013 Jan; 72(1):51-56. Disclosure of Interest: None declared